FACTORS RELATED TO STUNTING INCIDENCE IN CHILDREN UNDER-FIVE YEARS IN ARGODADI, SEDAYU, BANTUL - Pratama, Yanasta Yudo; Marwati, Tri Ani; Hidayat, Muhammad Syamsu (Universitas Ahmad Dahlan, 2021)
Background: Stunting is a chronic nutritional problem due to insufficient food intake with the standard nutritional needs - starting from pregnancy to 2 years of age. Stunting could be raising a lousy impact on children's health, inhibited brain development, motor development, and physical growth obstruction. Stunting is also harmful to national development because stunted children have low productivity and intelligence. This study aimed to determine the relationship between mother body height and the incidence of stunting in children aged 0-59 months in Argodadi, Sedayu, Bantul.Methods: This research was an observational analytic with a case-control design. This study population was all mothers who have toddlers aged 0-59 months. The population was 690 respondents. We recruited 154 samples using random sampling - consisting of 77 cases and 77 controls. Microtoise, infatometer, questionnaire, and WHO Anthro were used to collect the data. Data were analyzed using descriptive and chi-square tests.Results: The chi-square test shows that mother body height was associated with the incidence of stunting p-value 0.005 (p <0.05); OR: 3.2 CI (1.37- 7.52).Conclusions: Mother body height is a risk factor for stunting in children aged 0-59 months.